2007
DOI: 10.2466/pr0.101.4.1023-1030
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Norwegian Version of Hayes Ability Screening Index for Mental Retardation

Abstract: The Hayes Ability Screening Index was developed primarily to provide a short, effective screening test to indicate possible mental retardation amongst persons who come in contact with the criminal justice system. This study examined the validity of a Norwegian version in a sample of 73 subjects. 45 were male and 28 were female (M = 33.3 yr, SD = 12.5; range = 17 to 60 years) consecutively selected from patients referred for neuropsychological examination. The Wechsler Adult Intelligence Scale (WAIS-III) was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…This finding is congruent with results from previous studies (Ford et al, 2008;Sondenaa et al, 2007Sondenaa et al, , 2008Sondenaa et al, , 2011. The correlation of 0.69 in this study lies within the range of results of previous studies using the WAIS-III as a criterion of validity: Sondenaa et al (2007) found a correlation of 0.81 in a psychiatric setting, whereas Ford et al (2008) found a correlation of 0.55 in an adolescent offender sample. This study found that the HASI correlated both significantly, but better with verbal IQs than the performance IQs from the WAIS-III, which is in line with the findings of Sondenaa et al (2007).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This finding is congruent with results from previous studies (Ford et al, 2008;Sondenaa et al, 2007Sondenaa et al, , 2008Sondenaa et al, , 2011. The correlation of 0.69 in this study lies within the range of results of previous studies using the WAIS-III as a criterion of validity: Sondenaa et al (2007) found a correlation of 0.81 in a psychiatric setting, whereas Ford et al (2008) found a correlation of 0.55 in an adolescent offender sample. This study found that the HASI correlated both significantly, but better with verbal IQs than the performance IQs from the WAIS-III, which is in line with the findings of Sondenaa et al (2007).…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in contrast to the findings of Sondenaa et al (2007Sondenaa et al ( , 2008Sondenaa et al ( , 2011 and Ford et al (2008), who observed that with a higher cut-off score the HASI was too over-inclusive, and yielded a high number of false positives. They suggest lowering the cut-off score of 85 for better specificity.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations